Study of the relationship between the gamma ray bursts and their host galaxies - Nuza, Sebastian Ernesto (2005)
Gamma ray bursts (GRBs) belong to the most energetic events in the Universe. Recently, the extragalactic nature of these sources has been confirmed with the discovery of several host galaxies (HGs) and the measurement of their redshifts. To explain the origin of GRBs various models have been proposed, among which the coalescence of compact objects and the collapsar scenarios are the most representative, being the collapsar model one of the most accepted to explain the long duration GRBs. A natural consequence of this model is that the GRBs would trace the star formation rate (SFR) of their HGs. In this contributed paper we present preliminary results of the development of a Montecarlobased code for collapsar event formation which is coupled to chemical-cosmological simulations aiming at studying the properties of HGs in a hierarchical scenario.